2013
DOI: 10.1111/jzo.12020
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphisms in habitat‐specific morphology and behavior in the green anole lizard

Abstract: . (2013). Sexual dimorphisms in habitat-specific morphology and behavior in the green anole lizard. Journal Of Zoology, 290(2), 135-142. doi:10.1111/jzo.12020 Sexual dimorphisms in habitat-specific morphology and behavior in the green anole lizard AbstractSpecies that occur in variable environments often exhibit morphological and behavioral traits that are specific to local habitats. Because the ability to move effectively is closely associated with structural habitat, locomotor traits may be particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Zani () examined 85 lizard taxa and showed that decreases in toe length correlated with increases in clinging performance on rough substrates. Dill et al () also showed that toe length differs across habitats in A. carolinensis . Further studies are required to determine the functional role of differences in digit length among Anolis species.…”
Section: Discussionmentioning
confidence: 94%
“…Zani () examined 85 lizard taxa and showed that decreases in toe length correlated with increases in clinging performance on rough substrates. Dill et al () also showed that toe length differs across habitats in A. carolinensis . Further studies are required to determine the functional role of differences in digit length among Anolis species.…”
Section: Discussionmentioning
confidence: 94%
“…The association between physical attributes of the environment and morphology plays a large role in determining performance capabilities which, in turn, affect fitness (Arnold, ; Davis & Stamps, ; Dill et al ., ). Our findings suggest that previous studies of locomotor performance on level substrates (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, our study revealed that only females diverged in the number of foot lamellae in sympatry, emphasizing the fact that males and females may respond differently to the same perch height shift due to interspecific competition. Indeed, the interaction between traits may differ between the sexes, as it was shown in Anolis carolinensis for which the females -using broader perches -exhibited longer hindlimbs relative to SVL, while this relationship was exclusively allometric for males (Dill et al, 2013).…”
Section: Discussionmentioning
confidence: 99%